2021
DOI: 10.3390/cells10082131
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Glaucoma—Review of Anti-Fibrotic Processes and Bioenergetics

Abstract: Glaucoma is the leading cause of irreversible blindness globally. With an aging population, disease incidence will rise with an enormous societal and economic burden. The treatment strategy revolves around targeting intraocular pressure, the principle modifiable risk factor, to slow progression of disease. However, there is a clear unmet clinical need to find a novel therapeutic approach that targets and halts the retinal ganglion cell (RGC) degeneration that occurs with fibrosis. RGCs are highly sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 182 publications
(204 reference statements)
0
32
0
Order By: Relevance
“… 44 , 45 It is likely that the benefits of type 2 diabetes therapies, such as metformin, on POAG occur via mechanisms, such as fibrosis and mitochondrial bioenergetic dysfunction other than improved glycemic control. 46 , 47 Importantly, the genetic variants associated with fasting glucose and HbA1c we used in our analyses only account for a small proportion of the variance in these parameters. Besides, no significant association was found between genetically predicted glucose metabolism and POAG, perhaps due to the selection of fasting glucose and HbA1c related SNPs from non-diabetic populations.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 It is likely that the benefits of type 2 diabetes therapies, such as metformin, on POAG occur via mechanisms, such as fibrosis and mitochondrial bioenergetic dysfunction other than improved glycemic control. 46 , 47 Importantly, the genetic variants associated with fasting glucose and HbA1c we used in our analyses only account for a small proportion of the variance in these parameters. Besides, no significant association was found between genetically predicted glucose metabolism and POAG, perhaps due to the selection of fasting glucose and HbA1c related SNPs from non-diabetic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin reduced the SASP release caused by retinal ischemia and resulted in a significant decrease in SA-β-gal levels, thus preventing the adverse outcomes of ischemic retinopathy [ 22 ]. Although it has been proved to reduce the incidence rate of glaucoma in patients with type 2 diabetes through its anti-inflammatory, antiangiogenic, and antisenescent effects, there is no study showing the effect of metformin on glaucoma in nondiabetic patients [ 163 ]. Other antioxidants, such as resveratrol, vitamins D and E, curcumin, ginsenoside, and anthocyanins have also been shown to play a role in the protection against RGC death [ 164 ].…”
Section: Cellular Senescence As a Therapeutic Target In Glaucomamentioning
confidence: 99%
“…The secondary effects of metformin have been attributed to the activation of the metabolic regulator AMP-activated protein kinase and the potent antioxidant enzyme peroxiredoxin-2 [ 454 ]. Metformin has been proposed as a treatment for ocular conditions associated with mitochondrial dysfunction [ 455 , 456 , 457 ]. Retrospective studies have shown a modest trend of a reduced risk of AMD in subjects taking metformin, though confounding factors such as the presence of cardiovascular disease and diabetes have likely contributed to conflicting findings [ 458 ].…”
Section: Targeting Oxidative Stress In Agingmentioning
confidence: 99%